Numerical Investigations on Fluid Flow and Solidification Behavior during Impact of a Hollow Molten Droplet on a Solid Substrate - Patel, Virendra; ., . (International Journal of Engineering and Technology, 2018)
In thermal spraying coating process, powder materials are melted and driven towards the substrate’s surface. This process involves impact of liquid droplet and its solidification. In the past studies it has been reported that central counter jet present in the hollow droplet impact on substrate. This counter jet affects total solidification time of splat and spreading pattern. The objective of the present work is to develop a two dimensional CFD model to investigate the effect of surface roughness during spreading and solidification of molten ZrO2 hollow droplet impacting on a substrate of Stainless steel. The governing equations for fluid flow are solved numerically using a pressure-based finite volume method, following the SIMPLE algorithm presented by Patankar (1980). To track droplet THINC/WLIC method is used which is a VOF (Volume of Fluid) type method. To model surface tension force, the CSF (continuum surface flow) model is used. Enthalpy-based formulation is used to solve energy equation.